Potensi Desa Kuwiran Sebagai Kawasan Agrowisata Padi Berkelanjutan - Siswadi & Efrain Patola (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACTThe purpose of this research was to known : (1) to known potency a tour owned by CountrysideKuwiran As going concern Paddy Agrowisata Area., (2) to known response each perpetrator a tourto Countryside Kuwiran As going concern Paddy Agrowisata Area, (3) to known role from eachperpetrator wisata in realizing going concern operasionalisasi Paddy Agrowisata Area. Datacollecting of primary used technique of circumstantial interview (in depth interview) and have thecharacter of opened (open interview), while data collecting of secondary by citing tables or datawhich available from source of data.The results of this research show: : (1) countryside of Kuwiran very potential to becamePaddy Agrowisata Area have Continuation, good seen from attraction potency / object of tour,aksesibilitas, amenitas, and also hospitality, (2) local government response (On duty Tourism) tooperasionalisasi of Paddy Agrowisata Area, positive enough because although not yet there isgoals but have there is planning for the mentioned. While response of local society very positive,even expect immediately can be realized, (3) role of local government in